Tea polyphenols alleviate the adverse effects of diabetes on oocyte quality. Issue 9 (26th April 2022) - Lu, Jun; Zhao, Shu-Xian; Zhang, Man-Yu; Ji, Peng-Yuan; Chao, Shuo; Li, Li-Jun; Yin, Shen; Zhao, Lei; Zhao, Hua; Sun, Qing-Yuan; Ge, Zhao-Jia
Abstract : Maternal diabetes reduces oocyte quality. The decreased oocyte quality can be alleviated by tea polyphenols in vitro, such as mitochondrial function, meiosis, and DNA damage. Abstract : Maternal diabetes mellitus reduces oocyte quality, such as abnormalities of spindle assembly and chromosome segregation, mitochondrial dysfunction, decrease of fertilization rate, increase of ROS, and so on. So, it is important to research how to restore the decreased oocyte quality induced by maternal diabetes mellitus. Polyphenols are the most abundant bioactive components of green tea. It is reported that tea polyphenols have many health functions, for instance anti-oxidation, anti-inflammation, anti-obesity, and anti-diabetes. Thus, we hypothesize that tea polyphenols may play a crucial role in alleviating adverse effects of diabetes on oocyte quality. In the present study, we researched the effects of tea polyphenols on diabetic oocyte maturation in vitro . Compared with the control, oocytes from diabetic mice displayed a lower maturation rate and a higher frequency of spindle defects and chromosome misalignment. However, tea polyphenols significantly increased the oocyte maturation rate, and reduced the incidence of abnormal spindle assembly and chromosome segregation. Tea polyphenols also obviously decreased the reactive oxygen species (ROS) levels in diabetic oocytes, and increased the expression of antioxidant genes ( Sod1 and Sod2 ). Abnormal mitochondrial membrane potential was also alleviated in diabetic oocytes, and the expression of genes regulating mitochondrial fusion ( Opa1, Mfn1 and Mfn2 ) and fission ( Drp1 ) was significantly increased while tea polyphenols were added. Meanwhile, tea polyphenols reduced DNA damage in diabetic oocytes which may be mediated by the increased expression of Rad51, related to DNA damage repair. Our results suggest that tea polyphenols would, at least partially, restore the adverse effects of diabetes mellitus on oocyte quality.